1995
DOI: 10.1021/bi00031a023
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c Oxidase: Biphasic Kinetics Result from Incomplete Reduction of Cytochrome a by Cytochrome c Bound to the High-Affinity Site

Abstract: The electron-transfer kinetics of cytochrome c oxidase were probed by measuring the reduction levels of bound cytochrome c, cytochrome a, and cytochrome a3 during steady-state turnover. Our experimental approach was to measure these reduction levels as a function of (1) the rate of electron input into tightly bound cytochrome c by varying the concentration of TMPD (N,N,N',N'-tetramethyl-p-phenylenediamine) and/or cytochrome c and (2) the rate of electron efflux out of cytochrome a (true Kcat) by changing the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…3B). Second, the available data on cytochrome c oxidase do not disclose any evidence that the catalytic properties of the core enzyme were significantly refined in large and long‐lived mammals (Ortega‐Lopez & Robinson, 1995) as compared to short‐lived mammals (Gupte et al ., 1984), insects (Suarez et al ., 2000; Chamberlin, 2007), or even bacteria (Kadenbach et al ., 1991), which would agree with the fact that homeotherms are generally thought to carry more stable, but less efficient enzymes than poikilotherms (Suarez, 1996). On the contrary, higher animals rather seem to down regulate the catalytic core of their enzyme by means of nuclear‐encoded, regulatory subunits (Kadenbach et al ., 2000), indicating that the enzymatic activity of the catalytic subunits is far from limiting in these species (Gnaiger et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…3B). Second, the available data on cytochrome c oxidase do not disclose any evidence that the catalytic properties of the core enzyme were significantly refined in large and long‐lived mammals (Ortega‐Lopez & Robinson, 1995) as compared to short‐lived mammals (Gupte et al ., 1984), insects (Suarez et al ., 2000; Chamberlin, 2007), or even bacteria (Kadenbach et al ., 1991), which would agree with the fact that homeotherms are generally thought to carry more stable, but less efficient enzymes than poikilotherms (Suarez, 1996). On the contrary, higher animals rather seem to down regulate the catalytic core of their enzyme by means of nuclear‐encoded, regulatory subunits (Kadenbach et al ., 2000), indicating that the enzymatic activity of the catalytic subunits is far from limiting in these species (Gnaiger et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These approaches also have limitations. In the case of steady-state kinetics, a primary difficulty is incomplete reduction of cco redox centers by cyt c, due to the rate-limiting interaction between tightly bound cyt c molecules and the nonphysiological reductant normally used to initiate the reaction (Morgan and Wikstrom, 1991;Nicholls, 1993;Ortega-Lopez and Robinson, 1995). Because optical methods are usually based upon changes in the absorption spectrum of cco, which is dominated by heme a, such spectroscopic monitoring can only measure binding events related to this center (Malatesta et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It has to be emphasized, however, that none of these three models gives a completely satisfactory explanation of the experimental data. Furthermore, in a recent study, Ortega-Lopez and Robinson (1995) have clearly demonstrated that the biphasic kinetics and the requirement for additional electron transfer from excess cyt c during the low-affinity phase are a direct consequence of the limited rate of electron input into cco via a high-affinity cyt c molecule. In addition, the concept of two nonequivalent active sites on cco has been challenged repeatedly (Michel and Bosshard, 1989;Garber and Margoliash, 1990; Ortega-Lopez and .…”
Section: Introductionmentioning
confidence: 99%
“…Steady-state levels of cytochrome c were monitored at 550-540 nm, with dithionite used to attain full reduction. Cytochrome a was monitored at 605-630 nm; it was assumed that cytochrome a3 makes no contribution at this wavelength pair in the aerobic steady state [18], but contributes 15% after dithionite reduction.…”
Section: Methodsmentioning
confidence: 99%